Transfer research as an element of comparative vocational education and training : an example of factors influencing the transfer of dual training approaches of German companies in China, India and Mexico - Wiemann, Kristina [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2020)
"This article deals with comparative vocational education and training (VET) research on the international transfer of the dual training system. The article focuses on the question, which factors influence the possible transfer of dual training approaches in German multinational subsidiaries from a company-specific perspective. Based on the current state ofresearch, a brief overview of the research history and the theoretical background is given. The article specifies the outlined research question for China, India and Mexico with a focus on the mechanical engineering and plant construction sectors, the automotive and automotive supply sectors as well as the electronics and chemicals sectors. Using a qualitative research approach, expert interviews with 149 training experts of subsidiaries of German production companies were conducted, factory tours and visits to training facilities took place and document analyses rounded off the recording instruments. The identified influencing factors for companies are presented and discussed on the basis of country-specific findings. As an aggregated overview, the main influencing variables within the company and externally are outlined. The overall reflection for the transfer of dual training approaches in the conclusion completes the article." (author's abstract ; BIBB-Doku)
Keywords: S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); G 1.2.4.2.1 Handel, Instandhaltung, Reparatur von Kfz und Gebrauchsgütern; G 1.2.4.1 Produktion und Gewinnung; G 1.2.4.1.4 Verarbeitendes Gewerbe; I 2.3.4 Asien; I 2.3.3 Lateinamerika; I 2.1 Deutschland; Bildungstransfer; Berufsschule; Berufsbildungssystem; Arbeitsmarkt; Maschinenbau; Anlagenbau; Automobilindustrie; Berufsfeld Elektronik; Chemische Industrie; Bundesrepublik Deutschland; China; Indien; Mexiko